Analisis Manfaat Pengaruh Sinar Matahari Terhadap Proses Perkecambahan Kacang Hijau - Thalia Ajeng Ayu Kencana Ayu Kencana; Sudarti Sudarti; Yushardi Yushardi (Universitas Nusantara PGRI Kediri, 2023)
The intensity of light will affect the physiological processes of the plant. When the light intensity is high, the leaf cells will be smaller, the amount of chlorophyll is less, and the thylakoids in the leaves clump so that this can affect the growth of mung bean plants. In order to compare the growth in a bright environment with the growth of green beans in a dark environment, this research on the advantages of the influence of sunlight on the germination process of green beans was conducted. Plants must have access to light in order to complete the process of photosynthesis. Because light interferes with the function of the growth hormone (auxin), plants that receive more light from the environment experience growth inhibition, resulting in shorter stems than plants that receive less light.